Nucleotide diversity and association genetics of Xyloglucan Endotransglycosylase/hydrolase (XTH) and cellulose synthase (CesA) genes in Neolamarckia cadamba. - SY, Tiong; WS, Ho; SL, Pang; J, Ismail (Asian Network for Scientific Information, 2014)
A detailed study was carried out to discover single nucleotide polymorphisms (SNPs) from Neolamarckia cadamba partial XTH (~1283bp) and CesA (778bp) DNA sequences and further associates those SNPs with basic wood density. Primers were designed in flanking the partial XTH and CesA genes from 15 N. cadamba trees. The amplified DNA fragments were sequenced and the basic wood density measurements were determined for each tree. The sequence variation analyses revealed that 34 SNPs (2.65% occurrence) and 3 SNPs (0.39% occurrence) were found in 15 partial genomic DNA sequences of NcXTH1 and NcCesA1, respectively. All the SNPs were discovered in both exon and intron regions. NcXTH1 examined sites showed higher nucleotide diversities of π = 0.00402 and θw = 8.919 when compared to NcCesA1 (π = 0.00127; θw = 0.9226). The LD decayed slowly with distance of polymorphic sites in a linear pattern with the mean R2 value of 0.000687. Association genetics study showed that 2 SNPs from NcXTH1 genes were significantly associated with basic wood density (p<0.05) of N. cadamba. Once the gene-associated SNP markers in NcXTH1 genes are validated, it could be potentially used as a tool in Gene-Assisted Selection (GAS) of N. cadamba trees. This study has also demonstrated that the candidate-gene based association genetics is a powerful approach to dissect complex adaptive traits for organism lacking a genome sequence or reference genomic resources.